PROFITABILITAS DAN ECONOMIC VALUE ADDED TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FARMASI DI BURSA EFEK INDONESIA - Jefri, Ulfi; Fatimah, Siti (Bussman Journal : Indonesian Journal of Business and Management, 2021)
The purpose of this resource is knowing side-effect of Return On Asset (ROA) and Economic Value Added (EVA) on Stock Return of pharmachy subsector manufature in Bursa Efek Indonesia (BEI) 2015-2020 in period. This methode is using kuantitative methode, while population in this research all pharmachy subsector companies which was listed in Bursa Efek Indonesia (BEI) which the total 10 companies. Where a the sample was taken by using samling purposive technic. There are 8 pharmachy companies which was listed in Bursa Efek Indonesia (BEI) by using financial report in period 2015-2020. Data collection methode is dicumentation and data analysis techniques whice was used, analysis description data, classic assumtion, multiple linear regression analyis, and hypothesis testing by using SPSS vers. 25 favour. The result of this research indicates that variable Return On Asset (ROA) and Economic Value Added (EVA) is required negative value, so that taking basic assumption is backward. We can conclude that is required value -Tcount < -Ttable -3,019 < -2.014 by sig. 0.004 < 0.05. By this case, it indicates that Ho declined and Ha received. On Economic Value Added variabel (EVA) value Tcount > Ttable (-0,858 > -2.014 by sig. 0.396 > 0.05 so that Ho declined and Ha received.The conclusion of this researching result is based on test result F, it wa proved that simultaneously was obtained Fcount > Ftable 4.558 > 3.20 and the grade of sig. 0.016 < 0.05. So that Ho declined and Ha received, and sinificant Return On Asset and Economic Value Added to Stock return